Modification of Refractory Concretes with Aeration Agents as a Method of Protection against the Phenomenon of Spalling - Paweł Ogrodnik; Aleksandra Powęzka; Bartosz Zegardło (Recycling, 2018)
The aim of the work is to carry out tests analyzing the effectiveness of introducing pores to concrete on eliminating explosive spalling of concrete in fire conditions. A fireproof concrete is designed, which contains aluminum cement and aggregate obtained from waste sanitary ware. A Microporan aerating agent is used to modify the concrete features. The tests are carried out on cubic samples with nominal dimensions 10 × 10 × 10 cm and cylindrical dimensions 10 × 20 cm. Three batches of test samples are prepared, with different levels of aeration of the concrete mixture, i.e., without an aeration agent, with 0.5% and a 1% amount of aeration admixture weighted relative to the amount of cement used. Samples of all batches are divided into two series and conditioned in two types of environments with different humidity levels: dry and humid. The article presents the results of strength tests of concrete samples that are subjected to high temperatures similar to the temperatures occurring in the fire environment. The process of heating the samples proceeds according to the standard curve showing the temperature rise during the standard fire. The soaking temperature is in the range of 20 to 1000 °C. After baking in the oven, the samples are tested on a strength machine. The authors carry out only pilot studies. Only results from destructive tests of compressive strength of a refractory concrete composite are presented. The simulation station for the fire impact is the PK-1100/5 high-temperature chamber furnace together with the control system and a computer station with temperature monitoring software. Samples are loaded with increasing temperatures, according to the “temperature–time” standard curve. The compressive strength test is used as a criterion for assessing the effectiveness of the aeration agent. Strength tests are carried out both on unheated and soaked conditions in different environments. This paper presents the results of laboratory tests that allow for the authors to determine the characteristics of the material being tested. The empirical data include, among others, testing of selected physical properties (water absorption of concrete) and mechanical properties (measurements of compressive strength before and after thermal load). Based on the results obtained, conclusions from the tests are formulated. The proposed considerations show that the modification of the composite by aeration is an effective preventive measure in relation to the phenomenon of explosive concrete spalling.